2016
DOI: 10.1002/jbt.21837
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane prevents quinolinic acid‐induced mitochondrial dysfunction in rat striatum

Abstract: Quinolinic acid (QA) triggers striatal neuronal death by an excitotoxic cascade that involves oxidative stress, which in turns is tightly linked to mitochondria. Mitochondrial dysfunction is a molecular feature described in several brain pathologies. In this work, we determined whether the sulforaphane-neuroprotective effect in the rodent experimental model of Huntington's disease induced by QA is associated with mitochondrial function preservation. We found that QA impaired mitochondrial function within 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 36 publications
1
18
0
1
Order By: Relevance
“…For example, sulforaphane increases both proteasome and autophagy activity levels in vivo by activating the Keap1-Nrf2-ARE pathways and inhibiting MAPK and NF-kB pathways, as shown in a number of different HD mouse models [94,95] . Sulforaphane was also shown to reduce quinolinic acid-induced mitochondrial dysfunction in rat striatum, conferring a neuroprotective effect [96] . Rolipram inhibits phosphodiesterase 4 (PDE4) thus activating protein kinase A to enhance proteasome activity indirectly and in a HD mouse model was shown to alleviate symptoms of neuronal dysfunction [97] .…”
Section: Therapeutic Approaches In Hd Targeting Upsmentioning
confidence: 99%
“…For example, sulforaphane increases both proteasome and autophagy activity levels in vivo by activating the Keap1-Nrf2-ARE pathways and inhibiting MAPK and NF-kB pathways, as shown in a number of different HD mouse models [94,95] . Sulforaphane was also shown to reduce quinolinic acid-induced mitochondrial dysfunction in rat striatum, conferring a neuroprotective effect [96] . Rolipram inhibits phosphodiesterase 4 (PDE4) thus activating protein kinase A to enhance proteasome activity indirectly and in a HD mouse model was shown to alleviate symptoms of neuronal dysfunction [97] .…”
Section: Therapeutic Approaches In Hd Targeting Upsmentioning
confidence: 99%
“…The study by Rajesh V was undertaken to examine the effect of SFP on cognitive impairment in zebra fish model using a novel method of fear conditioning, and it was observed that exposure to 25 μmol/L SFP prior to scopolamine could significantly maintain the memory of learned task, suggesting that SFP might be a novel agent for cognitive enhancement in Alzheimer's disease . The data of Luis‐García demonstrated that SFP effectively disrupted the mitochondrial dysfunction by preventing the decrease in respiratory control ratio, transmembrane potential, ability to synthesize ATP and the activity of mitochondrial complexes I, II and IV . As a promising molecule of Nrf‐2 activator, SFP itself can directly interact Keap1 through covalent modification of cysteine residues thiol group, force Nrf‐2 separating from Keap1 and then activate Keap1‐Nrf‐2/ ARE pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, they examined in detail whether SFN would be able to modulate the function of mitochondria in the experimentally induced status epilepticus. Luis-García et al (2017) found that SFN suppressed the quinolinic acid-induced excitotoxic cascade in striatal neurons in rats. Quinolinic acid is used in experimental models of Huntington's disease and causes hyperactivation of the N-methyl-D-aspartate (NMDA) receptors, which are closely related to excitotoxicity associated with mitochondrial dysfunction (Beal et al, 1991;Bordelon et al, 1997;Mishra and Kumar, 2014).…”
Section: Effects Of Sfn On Brain Mitochondria In In Vivo Experimentalmentioning
confidence: 94%